STUDENTS' STRATEGY IN LEARNING VOCABULARY - Tumiur Ririn Afriani Naibaho; Pennalia Sinambela; Atus Utani Siringoringo (English Language Teaching Prima Journal (ELT), 2019)
This research discussed in order to find out about the students’ strategies in deriving vocabulary. The study was conducted to find out what strategies used or applied by the students’ n learning vocabulary at SMK Immanuel Medan, to teach about vocabulary especially about tenses, and to know how important the dictionary for students when they learning vocabulary. The research was conducted at SMK Immanuel Medan. Descriptive qualitative research design was used in this research. The subject of this research were the students of SMK Immanuel Medan. The researchers took 24 students as the subject of research. In collecting the data for this research, the writer used open questionnaire as instrument for the research. The result of the research data showed that large number of language learners applied some strategies in learning vocabulary. Those strategies used were cognitive strategie, memories strategie, and metacognitive strategie.